Indian Research Information Network System (IRINS): Analysis of Academic Institutions in India - TYAGI, SUNIL (Qualitative and Quantitative Methods in Libraries; Vol 10 No 2 (2021): June Issue 2021, 2021)
Purpose: The present study sought to analyze the Indian Research Information Network System (IRINS) instances with special reference to universities in India. The article explores top departments, facultys publications and citations of individual university. Methodology: To undertake the present study, data were collected from the website of Indian Research Information Network System (IRINS) (https://irins.org/irins/irins_instances.php). The present study confined to 29 Universities in India, most of them are centrally funded by Government of India. The collected data were classified, analyzed and tabulated by using statistical methods. Findings: The finding shows that the Banaras Hindu University (BHU) holds the highest numbers of faculties 1022 (15.40%) and has the highest scholarly publications 16376 (20.68%) with Scopus citation 208604 (22.05%) and Crossref citation 175973 (23.26%). The department of physics, Banaras Hindu University has the highest scholarly resources 2508(17.96%), whereas, the department of physics and astrophysics, University of Delhi has the highest 107 h-index with 1347 scholarly resources. Originality/value: This paper investigates trends in the research information management in universities in India with the context of IRINS that unfamiliar to many library and information science (LIS) professionals, and puts them in the context of professional practice.